2018
DOI: 10.1002/chem.201804226
|View full text |Cite
|
Sign up to set email alerts
|

On Jeff=0 Ground State Iridates(V): Tracking Residual Paramagnetism in New Bi2NaIrO6

Abstract: Open-shell transition metal oxides are capable of developing a rich diversity of electronic phases. The specific features evolving crucially depend on an intricate interplay of various local and long-range electronic interactions. Recently, the 5d transition elements have come into sharp focus because for these elements spin-orbit coupling (SOC) and onsite Coulomb repulsion (U) are on a comparable energy scale. For Ir the t level associated to an octahedral crystal field (CF) is split by SOC, giving rise to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…with Ir 5+ oxides. 12 Applying density functional band structure calculations, we can clearly assign a 5d 6 6s 0 configuration to the Pt atoms, consistent with a non-magnetic state.…”
Section: Introductionmentioning
confidence: 67%
“…with Ir 5+ oxides. 12 Applying density functional band structure calculations, we can clearly assign a 5d 6 6s 0 configuration to the Pt atoms, consistent with a non-magnetic state.…”
Section: Introductionmentioning
confidence: 67%
“…This has been encountered for 5 d 4 ions like Ir 5+ . [ 14 , 15 ] Also for Os 6+ (5 d 2 ) a nonmagnetic ground state owing to a combined action of spin‐orbit coupling and cubic crystal field (10 Dq ) has been reported. [ 16 , 17 , 18 ] The character of this state, however, is distinctly different from what we have in Na 9 Bi 5 Os 3 O 24 : it is not a singlet state with S = 0 , but a non‐Kramers e g doublet.…”
Section: Resultsmentioning
confidence: 99%
“…Single crystals of Ba 2 YIrO 6 , Sr 2 YIrO 6 , and Bi 2 NaIrO 6 and polycristalline samples of Sr 2 FeIrO 6 , and SrLaBIrO 6 with B=(Ni, Zn) were grown following the procedures as described in the literature [8,9,16,17,36].…”
Section: Methodsmentioning
confidence: 99%
“…For compounds with the formal Ir 5+ valency, the analogous picture leaves the j ef f = 3/2 bands fully filled while the j ef f = 1/2 doublet remains empty, producing a Van Vleck singlet ground state with J ef f = 0 [8][9][10]. Interestingly, a theoretical study presented yet the possibility of the presence of excitonic magnetism in such systems [11], and some experimental studies reported also FIG.…”
Section: Introductionmentioning
confidence: 92%